PENERAPAN METODE MIND MAPPING DALAM PEMBELAJARAN MENULIS TEKS ANEKDOT PADA SISWA KELAS X DI MA NURUL FALAH CIMAHI - Mega Rizky; Mila Nurjani; Sary Sukawati (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2019)
The background of this research is the difficulty of students in writing anecdotal texts. Writing is one aspect of language skills. Students are not optimal in writing anecdotal texts. Did the mind mapping method succeed in improving the skills of writing anecdotal texts? To find out the results of applying mind mapping methods to learning to write anecdotal texts. Researchers use the method of pre-experimental designs (One-Group Pretest-Posttest Design) as a research design that applies the initial test and final test. The results of this study compare before and after being given treatment to students with the results of the assessment of learning implementation Students who are better able to write anecdotal texts using the mind mapping method in the learning process. This is evident from the results of the average pre-test score of 63.65 and the average post-test score of 78.84. Paired T-test sample test through SPSS shows that the value of sig.0,000 <0.05 means that there are differences in the results of the pre-test and post-test values after being treated. This means that mind mapping is good for writing anecdotal texts. Writing anecdotal text using the mind mapping method was successfully implemented.